OPTIMASI COMMUNITY BASED TOURISM DAN PENGUATAN UMKM BERBASIS ONE VILLAGE ONE PRODUCT UNTUK MENGEMBANGKAN PARIWISATA BERKELANJUTAN DESA BANYUANYAR BOYOLALI - Dina Rahmasari; Kenny Reyza Feranda; Tifani Rizki Dianisa; Merinda Putri Dewi; Yundha Rachmawati; Aditya Wisnu; Fitri Wulandari; Manda Ardianingrum; Putri Balqis Salsabila; Tsabbita Ahmilul Husna; Akri Winarto; Akhmad Faahim Fannani; Kadek Merry Parwati; Kharisma Mayang (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2023)
Abstract The establishment of Banyuanyar Village as a tourism village is a form of realization of the mandate contained in the 2020-2024 RPJMN. The designation, which was made two years ago, has not yet provided significant income generation due to the absence of tourist destinations as leverage for tourist visits and the limited scale of production and marketing of UMKMs because they do not yet have business legality. Based on these problems, the PPK Ormawa KSP